Method for improving rotating bending fatigue strength of high-strength TC21 alloy
Through the combination of ultrasonic rolling and ultra-high frequency electromagnetic induction heating, a multiple gradient structure is formed, which solves the problem of insufficient fatigue strength of TC21 alloy under rotary bending fatigue conditions, and significantly improves its rotary bending fatigue strength and service performance.
Patent Information
- Application Number
- CN202411597167.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-07-04
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-11
AI Technical Summary
High-strength TC21 alloy is prone to fatigue damage under rotational bending fatigue conditions, resulting in failure of components, and the prior art is difficult to effectively improve its rotational bending fatigue strength.
Ultrasonic rolling increases the hardness of the surface layer of the material and introduces residual compressive stress to reduce the probability of fatigue cracks. At the same time, the sheet layer + bistate tissue transition area is formed under ultra-high frequency electromagnetic induction heating, extending the fatigue extension life.
It significantly improves the rotation bending fatigue strength and service performance of TC21 alloy, extends the material's rotation bending fatigue life, and enhances the surface's ability to resist the initiation of spin bending fatigue cracks and the internal crack propagation ability.
Smart Images

Figure CN119411049A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of multi-gradient structures of TC21 alloys, and in particular relates to a method for improving the rotational bending fatigue strength of high-strength TC21 alloys. Background Art
[0002] High-strength TC21 titanium alloy is a high-strength, high-toughness, damage-tolerant titanium alloy jointly developed by the Northwest Institute of Nonferrous Metals, Beijing Institute of Aeronautical Materials and other institutions. It has excellent mechanical properties and processing properties, especially good comprehensive performance of dual-state structure, high plasticity and impact toughness, and has become an important representative of high-performance engineering materials. In recent years, TC21 alloy, as an important structural material, has been widely used in aerospace and other fields, and has been made and used as important components, such as bearings, axles, drive shafts and other rotating parts. High-cycle fatigue damage is one of the important problems faced by TC21 alloy during use, especially under the conditions of high-cycle fatigue of rotational bending, the material is subjected to a complex stress state, and strengthening the fatigue performance of the material has become an inevitable choice to further expand the use scenarios of titanium alloys.
[0003] Rotating components such as bearings, axles, and drive shafts are often subjected to reciprocating torque during their service. For example, rotating components such as drive shafts are subjected to periodic rotational bending stress during actual operation. This stress can cause fatigue damage to the material during long-term use, thereby leading to component failure.
[0004] Therefore, how to improve the rotational bending fatigue life of the material while also allowing the core of the material to have high strength and toughness of the dual-state structure has become a core issue that needs to be urgently addressed in the torsional fatigue damage resistance structure and organizational design of high-strength TC21 alloy. Summary of the invention
[0005] In view of the above technical problems, the present invention proposes a method for improving the rotary bending fatigue strength of high-strength TC21 alloy. The surface hardness of the material is increased by ultrasonic rolling, and the residual compressive stress is introduced to reduce the probability of fatigue crack initiation. Secondly, the lamellar + dual-state structure transition zone is formed under ultra-high frequency electromagnetic induction heating to extend the fatigue extension life and improve the service performance of titanium alloy under rotary bending fatigue load.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention:
[0008] A method for improving the rotational bending fatigue strength of a high-strength TC21 alloy, wherein the TC21 alloy having a multi-gradient structure is obtained by combining ultra-high frequency electromagnetic induction heating and ultrasonic rolling.
[0009] The ultrasonic rolling has a rolling frequency of 1 to 15 passes, a static pressure of 300 to 700 N, a spindle speed of 100 to 360 n / min, a current of 0.35 to 0.5 A, and a frequency of 20 to 30 KHz.
[0010] Preferably, the ultrasonic rolling is performed 10 times, the static pressure is 500N, and the spindle speed is 200n / min.
[0011] Preferably, the method comprises the following steps:
[0012] The TC21 alloy (dual-state titanium alloy, the same below) is subjected to ultra-high frequency electromagnetic induction heating, cooling and aging treatment in sequence to form a first layer of gradient structure; the TC21 alloy forms an overall gradient structure with a gradual transition from the surface to the core of the lamellar structure, the lamellar structure + dual-state structure and the dual-state structure; the temperature of the ultra-high frequency electromagnetic induction heating is 20 to 50° C. higher than the phase transition point of the TC21 alloy, preferably 30° C., and the frequency is 600 to 1100 KHz;
[0013] The alloy after forming the first layer of gradient organizational structure is subjected to ultrasonic rolling to form a nano-fine-grained gradient organizational structure on the surface; that is, a second layer of gradient organizational structure is constructed on the surface organization of the first layer of gradient organizational structure, thereby forming a multiple gradient organizational structure.
[0014] Furthermore, the microstructures of the TC21 alloy with multiple gradient structures are: nano-fine grain gradient structure, lamellar structure, transition structure and dual-state structure from the surface to the core.
[0015] Furthermore, the thickness of the nano-fine-grained gradient structure is 50 to 120 μm, the hardness is 550 to 510 HV, and the roughness is 0.15 to 0.45 μm.
[0016] Furthermore, the thickness of the nano-fine-grained gradient structure is 100 μm, the hardness is 520 HV, and the roughness is 0.18 μm.
[0017] Preferably, the holding time of the ultra-high frequency electromagnetic induction heating is 1 to 3 seconds, and the frequency is 600 to 1100 KHz.
[0018] Preferably, the ultra-high frequency electromagnetic induction heating is performed in a SYG-10AB and CR2100 Series ultra-high frequency induction heating system.
[0019] Preferably, the cooling rate is 500-600° C. / s.
[0020] Preferably, the aging treatment is carried out at a temperature of 450 to 620° C. and for a time of 5 to 6 hours.
[0021] Preferably, the fatigue strength of the TC21 alloy with multiple gradient structures under rotational bending load is 760 MPa.
[0022] The second technical solution of the present invention:
[0023] A TC21 alloy with high rotational bending fatigue strength obtained by the above method presents nano gradient structure, lamellar structure, transition zone and dual-state structure from the surface to the core; the thickness of the nano gradient structure is 100 μm.
[0024] The third technical solution of the present invention:
[0025] The TC21 alloy having high rotational bending fatigue strength is used in the preparation of rotating parts of aerospace equipment.
[0026] Compared with the prior art, the present invention has the following advantages and technical effects:
[0027] In view of the stress characteristics and damage mode of rotational bending fatigue (the surface stress is the largest, cracks initiate from the surface and then expand toward the inside), the present invention proposes a structural design of multiple gradient organizations in which the material surface has strong resistance to rotational bending fatigue initiation, the sub-surface has high resistance to crack expansion and a high-strength and tough core; according to the organizational structure design, combined with the effects of separate surface ultra-high frequency induction heating and ultrasonic rolling technology on the gradient organization of the material, a mixed surface strengthening method is adopted to finally prepare a multiple gradient organizational structure.
[0028] The present invention adopts a method combining ultra-high frequency electromagnetic induction heating with ultrasonic rolling, so that the material forms a multi-gradient organization structure composed of rolled nano-gradient organization, lamellar organization, lamellar + dual-state organization and dual-state organization gradually transitioning from the surface to the core. The surface nano-gradient organization after rolling can reduce the probability of crack initiation, and the internal lamellar dual-state transition organization can increase the resistance to crack propagation, thereby extending the material's rotational bending fatigue performance and improving the material's rotational bending fatigue performance.
[0029] The present invention not only retains the high strength and toughness of the dual-state structure of the original titanium alloy material, but also improves the surface resistance to rotational bending fatigue crack initiation and the internal resistance to rotational bending fatigue crack propagation.
[0030] The present invention flexibly combines the traditional ultrasonic rolling process with the novel ultra-high frequency electromagnetic induction heating technology, so that the present invention combines the advantages of the two processes, while ensuring good process controllability and simple production methods, and promoting large-scale application of new technologies. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0032] Figure 1 Schematic diagram of the microstructure of TC21 after ultra-high frequency electromagnetic induction heating in Example 1 of the present invention;
[0033] Figure 2 The effect of different rolling parameters on the hardness and roughness of TC21 alloy after ultra-high frequency electromagnetic induction heating in Example 2 of the present invention;
[0034] Figure 3 The schematic diagram of the microstructure of the original TC21 alloy after ultrasonic rolling using the parameters of 500N static pressure, 200n / min rotation speed and 10 passes in Example 2;
[0035] Figure 4 This is a residual stress distribution diagram after ultrasonic rolling under the parameters of static pressure 500N, rotation speed 200n / min, and pass 10 times in Example 2 of the present invention;
[0036] Figure 5 Schematic diagram and microstructure of multiple gradient tissue in Example 3 of the present invention;
[0037] Figure 6 The rotary bending fatigue SN curves of the original TC21 alloy ultrasonic rolling (ultrasonic rolling) and the original TC21 alloy (original sample) are for the multiple gradient structure (induction heating + ultrasonic rolling) in Example 3 of the present invention, using the parameters of static pressure 500N, rotation speed 200n / min, and 10 passes in Example 2. DETAILED DESCRIPTION
[0038] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0039] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0040] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0041] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0042] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0043] The present invention provides a method for improving the rotational bending fatigue strength of a high-strength TC21 alloy, comprising the following steps:
[0044] The dual-structure titanium alloy (TC21 alloy) is subjected to ultra-high frequency electromagnetic induction heating, cooling and aging treatment in sequence to form a first layer of gradient structure; wherein the dual-structure titanium alloy forms an overall gradient structure that gradually transitions from lamellar structure, lamellar structure+dual structure and dual structure from the surface to the core; the temperature of the ultra-high frequency electromagnetic induction heating is 20 to 50° C. higher than the phase transition point of the dual-structure titanium alloy, preferably 30° C., and the frequency is 600 to 1100 KHz;
[0045] The alloy after forming the first layer of gradient organizational structure is subjected to ultrasonic rolling to form a nano-fine-grained gradient organizational structure on the surface; that is, a second layer of gradient organizational structure is constructed on the surface organization of the first layer of gradient organizational structure, thereby forming a multiple gradient organizational structure.
[0046] In some preferred embodiments, the phase transition point of the dual-state structure of the TC21 alloy is 970±5°C.
[0047] In some preferred embodiments, the TC21 alloy is preferably prepared into a rod shape to prepare for subsequent ultra-high frequency electromagnetic induction heating and ultrasonic rolling.
[0048] In some preferred embodiments, the holding time of ultra-high frequency electromagnetic induction heating is preferably 1 to 3 seconds, and the frequency is 800 to 1100 KHz.
[0049] In some preferred embodiments, the ultra-high frequency electromagnetic induction heating is preferably performed in a SYG-10AB and CR2100 Series ultra-high frequency induction heating system.
[0050] In some preferred embodiments, the cooling rate is preferably 500-600° C. / s.
[0051] In some preferred embodiments, the temperature of the aging treatment is preferably 450-620° C., more preferably 520° C., and the time is preferably 5-6 h, more preferably 6 h.
[0052] In some preferred embodiments, the static pressure of ultrasonic rolling is preferably 300-700N, more preferably 500N; the rotation speed is preferably 100-360n / min, more preferably 200n / min; the current is preferably 0.35-0.5A, more preferably 0.5A; the frequency is preferably 20-30KHz, more preferably 27.2KHz; the rolling passes are preferably 1-15 times, more preferably 10 times.
[0053] In some preferred embodiments, ultrasonic rolling can form ultra-high strength and ultra-hard nano-fine grain gradient structures.
[0054] In some preferred embodiments, the thickness of the nano-fine crystal gradient structure is preferably 100 μm.
[0055] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.
[0056] The "parts" described in the present invention, unless otherwise specified, refer to parts by mass.
[0057] The raw materials used in the present invention are all purchased from the market.
[0058] The technical solution of the present invention is further illustrated by the following embodiments.
[0059] Example 1
[0060] The TC21 alloy specimens with rod-like dual-state structure were heated to 1000℃ above the phase transformation point (970±5℃) by SYG-10AB and CR2100 Series ultra-high frequency induction heating systems, kept warm for 1.8s, and then rapidly cooled to room temperature at 600℃ / s. They were then aged in a muffle furnace at an aging temperature of 520℃ for 6h.
[0061] Figure 1Schematic diagram of the microstructure of TC21 after ultra-high frequency electromagnetic induction heating in Example 1 of the present invention; it can be seen from the figure that the rod-shaped sample is kept warm above the phase transition point for a short time to induce phase transition, so that the dual-state structure on the surface of the rod-shaped sample is transformed into a lamellar structure, while the sub-surface is a transition zone and the core is still a dual-state structure, thereby obtaining a gradient structure structure of a lamellar structure layer, a lamellar + dual-state structure layer and a dual-state structure.
[0062] Example 2
[0063] In this embodiment, the TC21 alloy rod sample with gradient structure after induction heating in Example 1 was ultrasonically rolled using surface ultrasonic rolling technology (wherein the current was 0.5A and the frequency was 27.2KHz). Other parameters are detailed in Table 1.
[0064] Table 1
[0065] Serial number Rolling times (times) Static pressure(N) Spindle speed (n / min) 1 1 500 100 2 5 500 100 3 10 500 100 4 15 500 100 5 10 400 100 6 10 600 100 7 10 700 100 8 10 500 150 9 10 500 200 10 10 500 250
[0066] Figure 2 The effects of different rolling parameters (using a single factor variable for control, for example, when the variable is the number of rolling times, the static pressure and the rotation speed are fixed to the optimal values, 500 N and 200 n / min, respectively; the same applies to the others) on the hardness and roughness of the TC21 alloy in Example 2 of the present invention;
[0067] Figure 3 The schematic diagram of the microstructure of the TC21 alloy after ultrasonic rolling of the original sample using the parameters of static pressure 500N, rotation speed 200n / min, and pass 10 times in Example 2;
[0068] Figure 4 This is a residual stress distribution diagram after ultrasonic rolling under the parameters of static pressure 500N, rotation speed 200n / min, and pass 10 times in Example 2 of the present invention;
[0069] Combination Figure 2-4 It can be seen that the optimal parameters of ultrasonic rolling are static pressure 500N, rotation speed 200n / min, and pass 10. The surface nano-gradient structure with ultra-high strength and ultra-hardness of 100μm thickness is formed on the surface of the material, and the hook-shaped residual stress is formed from the surface to the core, which can reduce the probability of fatigue crack initiation.
[0070] Example 3 (optimal parameters found by Example 2)
[0071] On the basis of the first layer of gradient organization structure prepared in Example 1, surface ultrasonic rolling was performed again, and the specific parameters of ultrasonic rolling were: static pressure 500N, rotation speed 200n / min, current 0.5A, frequency 27.2KHz, 10 passes, and a organization with a thickness of 100μm was formed on the surface. That is, the TC21 alloy finally presented nano gradient organization (hardness: 550-520HV; surface roughness: 0.18μm), lamellar organization, transition zone, and dual-state organization from the surface to the core, and finally formed a multi-gradient organization structure with overall high rotational bending fatigue performance from the surface to the core.
[0072] Figure 5 It is a schematic diagram of the multiple gradient organization in Example 3 of the present invention. It can be seen from the figure that between the coarse lath α sheets in the multiple gradient organization morphology is β transformation organization, which is composed of fine needle-shaped α sheets and β matrix, thereby improving the fatigue performance of TC21 alloy.
[0073] Figure 6 The rotary bending fatigue SN curves of the original TC21 alloy ultrasonic rolling (ultrasonic rolling) and the original TC21 alloy (original sample) are for the multiple gradient structures (induction heating + ultrasonic rolling) in Example 3 of the present invention, using the parameters of static pressure 500N, rotation speed 200n / min, and 10 passes in Example 2. The test method is carried out in accordance with the national standard GB / T4337-2015 "Rotary Bending Method for Fatigue Test of Metallic Materials". When conducting fatigue experiments, the stress of each fatigue sample increases or decreases by 10-50MPa compared to the previous sample. When the nth sample reaches the specified number of cycles under bending stress without breaking, and the stress values of the nth sample and the n-1th sample differ by no more than 10MPa, it is considered that the stress value corresponding to the nth sample is the fatigue limit value. From Figure 6 It can be seen that the fatigue life and fatigue strength after ultra-high frequency induction heating combined with ultrasonic rolling treatment are higher than those of pure ultrasonic rolling and the original state. The original state sample has improved its spin bending fatigue performance after ultrasonic rolling, and the original state sample has significantly improved its spin bending fatigue performance after ultra-high frequency electromagnetic induction heating combined with surface ultrasonic rolling treatment. Based on this, the comparison of spin bending fatigue performance further confirms the process from design to preparation of the multi-gradient organization in the present invention.
[0074] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for improving the rotary bending fatigue strength of high-strength TC21 alloy, characterized in that: By combining ultra-high frequency electromagnetic induction heating and ultrasonic rolling, TC21 alloy with multiple gradient structures was obtained. The ultrasonic rolling process has a rolling frequency of 1 to 15 times, a static pressure of 300 to 700 N, and a spindle speed of 100 to 250 n / min.
2. A method for improving the rotary bending fatigue strength of high-strength TC21 alloy according to claim 1, characterized in that: The ultrasonic rolling was performed 10 times, the static pressure was 500N, and the spindle speed was 200n / min.
3. The method for improving the rotary bending fatigue strength of high-strength TC21 alloy according to claim 1, characterized in that: The method comprises the following steps: The TC21 alloy is subjected to ultra-high frequency electromagnetic induction heating, cooling and aging treatment in sequence to form the first layer of gradient microstructure; The alloy after forming the first layer of gradient structure is subjected to ultrasonic rolling to form a nano-fine-grained gradient structure on the surface, thereby forming a TC21 alloy with multiple gradient structures.
4. A method for improving the rotary bending fatigue strength of high-strength TC21 alloy according to claim 3, characterized in that: The microstructures of the TC21 alloy with multiple gradient structures are: nano-fine grain gradient structure, lamellar structure, transition structure and dual-state structure from the surface to the core.
5. A method for improving the rotary bending fatigue strength of high-strength TC21 alloy according to claim 4, characterized in that: The thickness of the nano-fine crystal gradient structure is 50-120 μm, the hardness is 550-510 HV, and the roughness is 0.15-0.45 μm.
6. A method for improving the rotary bending fatigue strength of high-strength TC21 alloy according to claim 5, characterized in that: The thickness of the nano-fine-grained gradient structure is 100 μm, the hardness is 520 HV, and the roughness is 0.18 μm.
7. The method for improving the rotary bending fatigue strength of high-strength TC21 alloy according to claim 1, characterized in that: The temperature of the ultra-high frequency electromagnetic induction heating is 30° C. higher than the phase transition point of the TC21 alloy.
8. The method for improving the rotary bending fatigue strength of high-strength TC21 alloy according to claim 6, characterized in that: The fatigue strength of the TC21 alloy with multiple gradient structures under rotational bending cyclic load is 760 MPa.
9. A TC21 alloy with high rotational bending fatigue strength obtained by the method according to any one of claims 1 to 8, characterized in that: From the surface to the core, nano gradient tissue, lamellar tissue, transition zone and dual-state tissue are presented in sequence; the thickness of the nano gradient tissue is 100 μm.
10. Use of the TC21 alloy with high rotational bending fatigue strength as claimed in claim 9 in preparing rotating parts of aerospace equipment.